THE ROLE OF SADRIDDIN AYNI IN THE WORLD LITERATURE AND CULTURE HISTORY - Temirov Farrux Umedovich (Western European Studies, 2024)
Sadriddin Ayniy (1878-1954) is one of the people who made a great contribution to the development of science, culture and spirituality in ancient and modern Bukhara and spread its word to the world. He is widely known among the peoples of Central Asia, and he is one of the many poetic, prose, historical, scientific and creative creators who created in Uzbek and Tajik languages that the literature of the peoples living in this large area deserves to be on the world stage
Keywords: literature; people; prose; deserves